Adjuvant and neoadjuvant therapy for biliary tract cancer: a review of clinical trials - Nara, Satoshi; Esaki, Minoru; Ban, Daisuke; Takamoto, Takeshi; Shimada, Kazuaki; Ioka, Tatsuya; Okusaka, Takuji; Ishii, Hiroshi; Furuse, Junji (Japanese journal of clinical oncology, 2020)
Cancer originating in the biliary tract can be classified as bile duct cancer (cholangiocarcinoma), gallbladder cancer, or ampullary cancer. Bile duct cancer is further divided to intrahepatic, perihilar and distal bile duct subtypes according to the anatomical location of the tumor. The biological characteristics of each tumor are heterogeneous. However, because of the rarity of each disease, the efficacy of new drugs has been tested in groups of patients with different biliary tract cancers. In patients with metastatic or recurrent biliary tract cancer, recent randomized clinical trials revealed the non-inferiority of gemcitabine + S-1 and the superiority of gemcitabine + cisplatin + S-1 compared with gemcitabine + cisplatin in terms of overall survival, thereby establishing a new standard treatment. In the field of adjuvant therapy for biliary tract cancer, the British BILCAP (capecitabine compared with observation in resected biliary tract cancer) study revealed longer median overall survival in the capecitabine group than in the observation group in the per-protocol analysis (but not in the intention-to-treat analysis), bringing a shift toward postoperative management. Several other studies of adjuvant therapy are ongoing, and they may lead to reforms in treatment strategy for resectable biliary tract cancer in the future. The use of neoadjuvant therapy for biliary tract cancer is in its infancy, but it is expected to overcome the limitations of adjuvant therapy for this malignancy. In this review, we summarized the evidence available from clinical trials of adjuvant and neoadjuvant therapy for biliary tract cancer and described ongoing clinical trials.